Building condition assessment after conservation work at Masjid Lama Kampung Dal, Padang Rengas, Perak / Ahzahar, N , Zakaria, I. B. and Bahari, M.M - Ahzahar, N.; Zakaria, I. B.; Bahari, M. M (2012)
Masjid Lama Kampung Dal was built in year 1936 at the order of the 30th King of Perak, Sultan Iskandar Shah. The architecture design of the mosque is different from other typical mosque at that time because of its simple design with no dome and the walls are made of woven sliced bamboo in a diamond shaped pattern (kelerai). The mosque has been conserved started in 22 Dec 2008 and completed in 21 June 2009 with RM 786,100.00 cost funded by Jabatan Warisan Negara. After 3 years of conservation work, there is no current condition survey has been made. Therefore, this study is conducted to evaluate existing condition of the mosque according to Building Condition Survey CP BS101. The mosque is currently not being use for any function since a new replacement mosque is located nearby operating for local people. The study is done by assessing overall condition of the mosque and rated accordingly using Building Assessment Rating System (BARIS). This study is succeed in determining the existing condition of the mosque. From the survey, it can be concluded that the mosque is in fair condition which need minor repair. Furthermore timber decay has become the most occurred defect in the building. Apart from that, the mosque is also proposed to be open to public such as transform into a gallery in order to be able its architecture being appreciated by everybody considering government has spent so much money for its conservation work.